The effect of tunneling incentives and taxes on the indication of transfer pricing in LQ-45 companies for the 2019–2021 period - Ruth Christy Aritonang; Francis M. Hutabarat (Institute of Computer Science (IOCS), 2023)
The aim of this research is to find the effect of tunneling incentives and taxes on indications of carrying out transfer pricing in LQ-45 companies for the 2019–2021 period. Transfer pricing is used as the dependent variable, and tunneling incentives and taxes are used as the dependent variables. The sample of this research is LQ-45 companies indexed on the Indonesia Stock Exchange. There were 40 LQ-45 companies in the 2019–2021 observation year, with purposive sampling used to produce 120 samples under observation. Tunneling incentives were found to have an effect on transfer pricing decisions, while the tax variable had no effect on transfer pricing decisions.